Boundary Capabilities in MNCs: Knowledge Transformation for Creative Solution Development. (6th February 2017) - Tippmann, Esther; Sharkey Scott, Pamela; Parker, Andrew
Abstract: The management of knowledge across country units is critical to multinational corporations (MNCs). Building on the argument that boundary spanning leads to the development of creative problem solving outcomes, this study advances the concept of MNC knowledge transformation and examines its relationship with solution creativity. Using questionnaire data on 67 problem solving projects, we find that opportunity formation is an underlying mechanism linking MNC knowledge transformation to the development of creative solutions. These insights contribute to our understanding of boundary spanning in global organizations by substantiating MNC knowledge transformation and elaborating the relationship between boundary spanning and creative solution development. If successful at knowledge transformation, collaborators from across the MNC can construct previously unimagined opportunities for the generation of creative outcomes.